Using digital ethnography to research embodied information practices on social media - Laura Williams (Information Research: An International Electronic Journal)
Introduction. This paper discusses the use of digital ethnography to research the embodied information practices of ultrarunners. The paper considers the challenges of digital ethnography and explores how embodied and immersive methods could bring the body into digital ethnography.